2019
DOI: 10.1111/are.14204
|View full text |Cite
|
Sign up to set email alerts
|

Determination of grapefruit (Citrus paradisi) peel extract bio‐active substances and its application in Caspian white fish (Rutilus frisii kutum) diet: Growth, haemato‐biochemical parameters and intestinal morphology

Abstract: In this study, total phenolic and flavonoid contents of grapefruit peel extract (GPE) were equal to 117.3 ± 0.3 µg of gallic acid/mg and 39.30 ± 0.1 µg of quercetin/mg respectively. Caspian white fish (n = 180, 4 ± 0.9 g body weight) was fed with supplemented diets, including 0, 6.25, 12.5 and 25 mg of GPE/kg for 60 days at 25 ± 1°C. The growth performance was markedly improved in fish fed with 25 mg/kg of GPE compared to others (p < 0.05). Moreover, fish fed with 25 mg/kg of GPE showed a significant increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Serum measurements.-Total protein (TP), cholesterol, triglycerides, and glucose were estimated by using available commercial kits from Pars Azmoon Company (Alborz, Iran) and by using a Hitachi 917 automated biochemical analyzer (Hitachi, Tokyo) according to the manufacturer's guidelines (Samavat et al 2019). Complement components 3 and 4 (C3 and C4) were also measured by commercial diagnostic kits (Pars Azmoon) and the Hitachi 917 auto-analyzer in accordance with the manufacturer's instructions (Rashmeei et al 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Serum measurements.-Total protein (TP), cholesterol, triglycerides, and glucose were estimated by using available commercial kits from Pars Azmoon Company (Alborz, Iran) and by using a Hitachi 917 automated biochemical analyzer (Hitachi, Tokyo) according to the manufacturer's guidelines (Samavat et al 2019). Complement components 3 and 4 (C3 and C4) were also measured by commercial diagnostic kits (Pars Azmoon) and the Hitachi 917 auto-analyzer in accordance with the manufacturer's instructions (Rashmeei et al 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, lemon peel might be used to supplement fish feed with a low‐cost supply of vitamin C. Furthermore, bergamot essential oils are also a good source of bioavailable substances, such as, limonene, linalool, linalyl acetate and β‐pinene (Costa et al, 2010). In the same context, the addition of grapefruit ( Citrus paradise ) peel extract to Caspian white fish ( Rutilus frisii kutum ) diets at different levels (0, 6.25, 12.5 and 25 mg kg −1 diet) increased fish growth performance (Samavat et al, 2019). This is most likely linked to the increased nutritional digestion and absorption capabilities of the fish as a result of the healthy gut microbiota (MacLennan et al, 2002).…”
Section: Effects Of Suplemental Citrus Waste Products and Exctracts O...mentioning
confidence: 99%
“…The addition of essential oil extracted from C. limon peel up to 5% in diet was enhanced the biochemical, haematological and immunological responses in cyprinid fish Labeo victorianus fingerlings (Ngugi et al, 2017). Moreover, Samavat et al (2019) observed that adding grapefruit ( C. paradise ) peel extract (GFE) at a level of 25 mg kg −1 markedly enhanced the hemato‐biochemical indices including red blood cell (RBC) and white blood cell (WBC) counts, packed cell volume and haemoglobin (Hb) values of Caspian white fish ( R. frisii kutum ). As a result, it is possible that GPE activates the hematopoietic tissue of the fish.…”
Section: Effects Of Cwp and Extracts On Hemato‐biochemical Indicesmentioning
confidence: 99%
“…The fixed samples were sectioned into 4-5 μm and stained using haematoxylin-eosin. The intestinal tissue morphology was assayed by an inverted optical Eclipse TS100 imaging microscope (Nikon), and the taken photos were processed using the ImageJ software as described previously by Samavat et al (2019). The villus length (μm), crypt depth (μm), villus width (μm) and surface area (μm 2 ) were conducted.…”
Section: Intestinal Topographymentioning
confidence: 99%